2009
DOI: 10.2903/j.efsa.2009.1332
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the re-evaluation of Azorubine/Carmoisine (E 122) as a food additive

Abstract: The Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion re-evaluating the safety of Azorubine/Carmoisine (E 122). Azorubine/Carmoisine has previously been evaluated by JECFA in 1983 and the SCF in 1984. Both committees established an Acceptable Daily Intake (ADI) of 0-4 mg/kg bw/day. The Panel was not provided with a newly submitted dossier and based its evaluation on previous evaluations, additional literature that became available since then and the data available followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Samples KN1 and KN2 contained the same food color azorubine [19], while sample KN3 contained amaranth [11]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples KN1 and KN2 contained the same food color azorubine [19], while sample KN3 contained amaranth [11]. …”
Section: Resultsmentioning
confidence: 99%
“…The two isolated compounds are being referred to EFSA as amaranth (E123) and azorubine or carmoisine (Ε122) and are well-known food dyes [19, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…An acceptable daily intake of 4 mg/kg bw was establish for azorubine [111]. There is no evidence of mutagenic, carcinogenic or teratogenic properties for azorubine with histopathological effects, but in rare situations it seems to cause skin and respiratory allergic reactions [112]. Inetianbor et al [18] further reported, as possible negative effects of azurobine, DNA damage and tumours in animals.…”
Section: Azorubinementioning
confidence: 99%
“…The energy consumption per volume of effluent treatment was estimated and expressed in kW•h •dm −3 [32]. In the case of electro-oxidation, the plasma and sequenced treatment were taken into consideration for the estimation of energy consumption following Equation (3).…”
Section: Energy Consumption and Costmentioning
confidence: 99%
“…The azo dye Carmoisine is classified as azorubine (E122) and is also called acid red 14 or additive E122 in the European Union (EU) [3]; the chemical structure of Carmoisine is shown in Figure 1. The use of this red dye in the food industry has increased because of the coloration of confectionery, jams, candies, jellies, ice cream, soft drinks, alcoholic beverages, etc.…”
Section: Introductionmentioning
confidence: 99%